ANALYSIS OF SERVICE QUALITY IN AN EFFORT TO IMPROVE MEMBER SATISFACTION (CASE STUDY ON PT.PIM SHARIA EMPLOYEE COOPERATIVES) - Amelia, Amelia; Fadhillah, Indah; Pangestika, Ratri; Charunnisa, Zihan; Nur Ilham, Rico (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
In a cooperative, satisfactory service is the most important thing that needs to be considered for cooperatives to satisfy their customers or customers. Product and service services must be carried out properly and correctly so that they get sympathy and are attractive to the community of prospective customers concerned. If the service is carried out properly and correctly, the marketing of products and services is expected to be successful as well. Service is an activity or series of activities that are invisible (cannot be touched) that occur as a result of interactions between consumers and employees, or other things provided by service delivery companies that are intended to solve problems or customers. This research uses a qualitative research approach. where qualitative research as a scientific method is often used and carried out by a group of researchers in the field of social sciences, including education. A number of reasons were also put forward, which in essence is that qualitative research enriches the results of quantitative research. Qualitative research is conducted to build knowledge through understanding and discovery. Qualitative research approach is a process of research and understanding based on methods that investigate social phenomenon and human problems. In this study the researcher takes a complex picture, examines the words, reports detailed views of the respondents and conducts studies in natural situations. Qualitative research is carried out in natural conditions and is a discovery. In qualitative research, the researcher is the key instrument. Because of that researchers must have the provision of theory and broad insight so they can ask questions, analyze and construct the object being researched to be clearer. This research emphasizes more on meaning and bound by value. The essence of qualitative research is observing people in their environment interacting with them, trying to understand their language and interpretation of the world around them, approaching or interacting with people related to the research focus with the aim of trying to understand, explore their views and experiences to obtain information or data. what is needed Qualitative research where the role of the researcher is as a key instrument in collecting data, and interpreting data.Data collection tools usually use direct observation, interviews, document studies. While the validity and reliability of data using triangulation using inductive methods, the results of qualitative research emphasize meaning rather than generalization. Qualitative research is used if the problem is not clear, to find out hidden meanings, to understand social interactions, to develop theories, to ensure the correctness of data and to examine the history of development.